In vivo fate of free and encapsulated iron oxide nanoparticles after injection of labelled stem cells. Issue 1 (25th September 2018) - Ashraf, Sumaira; Taylor, Arthur; Sharkey, Jack; Barrow, Michael; Murray, Patricia; Wilm, Bettina; Poptani, Harish; Rosseinsky, Matthew J.; Adams, Dave J.; Lévy, Raphaël
Abstract : Free and encapsulated iron oxide nanoparticles after intracardiac injection of labelled stem cells have similar in vivo fate. Abstract : Nanoparticle contrast agents are useful tools to label stem cells and monitor the in vivo bio-distribution of labeled cells in pre-clinical models of disease. In this context, understanding the in vivo fate of the particles after injection of labelled cells is important for their eventual clinical use as well as for the interpretation of imaging results. We examined how the formulation of superparamagnetic iron oxide nanoparticles (SPIONs) impacts the labelling efficiency, magnetic characteristics and fate of the particles by comparing individual SPIONs with polyelectrolyte multilayer capsules containing SPIONs. At low labelling concentration, encapsulated SPIONs served as an efficient labelling agent for stem cells. The bio-distribution after intra-cardiac injection of labelled cells was monitored longitudinally by MRI and as an endpoint by inductively coupled plasma-optical emission spectrometry. The results suggest that, after being released from labelled cells after cell death, both formulations of particles are initially stored in liver and spleen and are not completely cleared from these organs 2 weeks post-injection.